A Review on Network Layer Attacks in Wireless Sensor Networks - K, Parvathy; Rajalakshmi, S (International Journal of Computer Sciences and Engineering, 2021)
The wireless sensor networks (WSN) are said to be one of the popular networks in using all-inclusive applications like lots of applications in environment monitoring, military applications, health care monitoring, habitat monitoring, etc. .These networks are structured in many or more number of sensor nodes. The Deployment of nodes in these networks are not secure which may cause to security attacks. In this paper, different types of attacks and network layer attacks are discussed in wireless sensor networks and how to enhance and detect the attacks from the WSN by using some of the methods to resolve the problem.